SMAS Harapan Utama Batam's Integrated Marketing Communication: Strategy Preference - Alyssa Saqina Nabila Parmadi; Hilda Yunita Wono (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
The establishment of Senior High Schools (SMA) plays an important role in creating a quality education system and honing students' creativity. In addition, high schools also serve as a place for students to develop social skills, critical thinking, and prepare themselves to face challenges at the next level of education. The competition between public and private high schools drives the need for effective Integrated Marketing Communication (IMC) strategies to attract prospective students. With the increasing number of schools, each educational institution must be able to build strong appeal and reputation in the community. SMAS Harapan Utama Batam has implemented IMC such as advertising, digital marketing, sales promotion, and direct marketing. Advertising is used to increase public awareness of the school through various media, both print and digital. Digital marketing is increasingly being optimized in line with changing trends in information consumption, especially through social media platforms. Sales promotions such as registration fee discounts become an additional strategy to increase the interest of prospective students. Meanwhile, direct marketing allows for a more personal interaction between the school and prospective students. This study aims to evaluate the IMC used by the school with a descriptive quantitative method, using a Likert scale and surveys of 106 parents and guardians. The results show the highest preference for digital marketing through TikTok, followed by advertising, digital marketing through Instagram, sales promotion, and direct marketing. This shows that social media plays a significant role in the school's marketing strategy. These findings are expected to serve as input for SMAS Harapan Utama and similar schools to enhance marketing effectiveness and increase the number of students in the future.   Keywords: Country, Education, High School, Integrated Marketing Communication, Preference.